Imageamento crustal da porção Sul da Bacia do Paraná e Escudo Sul-Rio-Grandense pelo método sismológico Função do Receptor - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The use of seismological methods to study the interior of the earth is a fundamental tool to understand the dynamics of the planet. The seismology contributed to the construction of the classical model of the internal structure of the earth from studies related to the propagation of seismic waves generated by earthquakes, such studies were able to identify the different inner layers of the planet. On a smaller scale, geophysical studies associated with crustal structure and composition are important for understanding the tectonic evolution of a region. In this context, the present work proposes the application of the Receiver Function seismological method in data recorded by eight seismographic stations, aiming to obtain values related to crust thickness and Vp / Vs ratio for the region of Rio Grande do Sul state. , encompassing the southern portion of the Paraná Basin and South-Rio-Grandense Shield. The Receiver Function method uses P waves generated by telessismic events, which, when focused on an interface that separates two media at different speeds, have part of their energy converted to S wave and the other part undergoes multiple reflections. From the time difference between the arrival of the P and Ps waves it is possible to obtain information about the internal structure of the Earth from the deconvolution between the register components. The seismological data used come from the BL network, using the ITQB, CPSB, CNLB and PLTB stations and from the XC network, where the RODS, UNIS, ALGR and CRSM stations were used, all located in the state of Rio Grande do Sul. The results obtained from the data processing show that the thickness of the crust in the state of Rio Grande do Sul varies from 36.6 km to 42 km, having an average Vp / Vs of 1.76. In the south-Rio-Grandense Shield region, the crustal thickness is approximately 36 km and Vp / Vs approximately 1.75. The southern region of the Paraná Basin has a crustal thickness of approximately 42 km and VpVs around 1.77. The obtained crustal thickness values demarcate the boundary between the Paraná Basin and the Sul-Rio-Grandense Shield and are correlated with topographic and gravimetric data and also corroborate the crustal thickness values obtained from previous work in the same area.
Keywords: Geofísica; Sismologia; Função do Receptor; Espessura Crustal; Geophysics; Seismology; Receiver Function; Crustal thickness; CNPQ::CIENCIAS EXATAS E DA TERRA